Seismic response sensitivity of the structures equipped with cylindrical frictional dampers to the value of slippage load - H. R. Samani; M. Mirtaheri (Numerical Methods in Civil Engineering)
Cylindrical Frictional Damper (CFD) is a new revolutionary frictional based mechanical damper. Unlike the other types of frictional dampers, CFDs do not utilize bolts to produce friction between contact surfaces. These dampers consist of two main parts, the inner shaft and the external cylinder. These two parts are assembled such that one is shrink-fitted inside the other. In this investigation, seismic response of steel structures equipped with CFDs is studied. Special attention is given to the sensitivity of the seismic response to the value of the slippage load. To do so, the optimum slippage load of the structure (the slippage loads which results in minimum displacement response) is obtained for various seismic excitations. The seismic response of the structure is obtained for various slippage loads in the range of plus and minus %20 of the optimum slippage load. Moreover the seismic performance of steel structures equipped CFDs is investigated using non-linear time history analyses. The results show that value of the optimum slippage load is completely dependent to seismic excitation. It is further shown that if the slippage load has a difference up to 20% from its optimum value, the maximum displacement response can increases up to 35%, however, it is still less than the maximum displacement response of the frame without CFDs. It was also shown that CFD can significantly improve the performance of steel structures subjected to earthquake loads.